A note on a family of non-gravitational central force potentials in dimension one. (December 2017) - Alvarez-Ramírez, M.; Corbera, M.; Cors, Josep M.; García, A.
Abstract: In this work, we study a one-parameter family of differential equations and the different scenarios that arise with the change of parameter. We remark that these are not bifurcations in the usual sense but a wider phenomenon related with changes of continuity or differentiability. We offer an alternative point of view for the study for the motion of a system of two particles which will always move in some fixed line, we take R for the position space. If we fix the center of mass at the origin, the system reduces to that of a single particle of unit mass in a central force field. We take the potential energy function U ( x ) = | x | β, where x is the position of the single particle and β is some positive real number.